Search and Optimisation with Smart Ant-Like Software Agents - Kin Lai, Weng; Meng Hoe, Kok; Mei Aw, Yit; Yin Tai, Tracy Sock (Malaysian Journal of Computer Science, 2002)
Simple organisms that live in colonies, for example ants, bees, wasps and termites have long fascinated many people for their collective intelligence that is manifested in many of the things that they do. Recently, computational paradigms based on the humble ant have been offered as a different approach to solve non-trivial engineering problems. This new computational paradigm replaces the traditional emphasis on control, preprogramming, and centralisation with designs featuring autonomy, emergence, and distributed functioning. A growing community of researchers has applied such swarm intelligence to solve a variety of diverse applications. This paper describes the development of a pair of ant-based algorithms that were used to solve two very different engineering problems in search and optimisation.